Sentido e participação na atividade de panificação das mulheres do empreendimento econômico solidário oito de junho sob a ótica da teoria social da aprendizagem - Paixão, Marcia Valéria (2014)
This study was born from the desire to understand the learning of subjects pertaining to economic enterprises born of the solidarity economy, specifically the productive group of rural women producers of the Settlement Eight June. The prospect of Social Learning Theory has revealed knowledge as a result of the active participation of individuals in communities of practice, in activity systems, and numerous questions were born in the search of this understanding, outlining a goal that translates to reveal the meaning of the activity and participation in an organizational form that escapes the traditional capitalist enterprises. Combining our epistemological assumptions with the proposals of Engestrom and Nicolini, form a methodological package coherent with a concrete and social man, a man who has voice, using ethnography and oral history as means to find the answers from the experiences of these individuals. The answers led us to reveal the meaning of the activity as the search for an identity, and a sense of participation by the desire for social affiliation. These senses are absorbed by other activity systems that form a web of collaboration that gives rise to a potentially shared object, generator of contradictions that lead women to question all the time the current activity, relating it to a future order. This relationship, connect with the elements of the context, incorporates new contradictions, causing the development of a learning activity and leading the activity system to an expansive cycle. And the revelation of the fugitive object potencial of industry showed a learning that borns of a force which aims at creating a qualitatively new pattern of activity to meet the subject of multiple systems, requiring the mediation of new theoretical concepts in order to extend the horizon of possibilities in the industry. Thus, joining the practice, materiality of their motives, the theory, composed of discussions to practical activity takes place, women have repositioned their forms of participation in social life, connecting to the outside world, promoting their learning. And to the extent that the object reaches more baking systems activities, add the desire to include more settled in the industry, more women move to a new proximal zone, in an expansive movement that causes transformation and leads to the creation of a collective project, remodeling the activity system and consolidating a new practice